Reliability of the Modified Star Excursion Balance Test in individuals with Down Syndrome. (October 2022) - Ozmen, Tarik; Gunes, Musa; Simsek, Ayse; Inceoglu, Feyza
Abstract: Neuromotor problems such as hypotonia, incoordination, impaired sensory-motor integration lead to significant delays in motor skills and balance development in individuals with Down Syndrome (DS). Balance control is essential for performing many motor skills independently and safely. Standardised testing of balance control can contribute significantly to the rehabilitation of individuals with DS. The purpose of this study was to determine intrarater and interrater reliability of the Modified Star Excursion Balance Test (SEBT) for individuals with DS. Thirteen individuals with DS were recruited in this study. Intraclass correlation coefficients (ICC [3, 1]) with 95% confidence intervals, standard error of measurement (SEM), the smallest detectable difference (SDD) and the Spearman rank correlation coefficient were calculated. In all directions of the Modified SEBT, no statistically significant difference was found between two raters' first and second measurements (p > 0.05). Interrater reliability for all reach directions of the Modified SEBT was high, with ICC ranging from 0.990 to 0.998.95% confidence intervals, SEM and SDD ranged from 0.924 to 0.999, 0.180–2.434 and 3.270–6.747, respectively. The Modified SEBT are reliable for evaluating dynamic balance in individuals with DS aged between 6 and 24 years.